Parallel‐reaction monitoring revealed altered expression of a number of epitranscriptomic reader, writer, and eraser proteins accompanied with colorectal cancer metastasis. Issue 3 (26th April 2022) - Qi, Tianyu F.; Tang, Feng; Yin, Jiekai; Miao, Weili; Wang, Yinsheng
Abstract: RNA contains more than 170 types of chemical modifications, and these modified nucleosides are recognized, installed and removed by their reader, writer, and eraser (RWE) proteins, respectively. Here, we employed a parallel‐reaction monitoring (PRM)‐based targeted proteomic method, in conjunction with stable isotope labeling by amino acids in cell culture (SILAC), to examine comprehensively the differential expression of epitranscriptomic RWE proteins in a matched pair of primary/metastatic colorectal cancer (CRC) cells, namely SW480/SW620. We were able to quantify 113 nonredundant epitranscriptomic RWE proteins; among them, 48 and 5 were up‐ and down‐regulated by >1.5‐fold in SW620 over SW480 cells, respectively. Some of those proteins with marked up‐regulation in metastatic CRC cells, including NAT10, hnRNPC, and DKC1, were documented to assume important roles in the metastasis of CRC and other types of cancer. Interrogation of the Clinical Proteomic Tumor Analysis Consortium data revealed the involvement of DUS1L in the initiation and metastatic transformation of CRC. It can be envisaged that the PRM method can be utilized, in the future, to identify epitranscriptomic RWE proteins involved in the metastatic transformations of other types of cancer.